L’inquietudine bestiale: "The Lobster" come esperienza dell’impersonale - Marra, Emilia (Philosophy Kitchen - Rivista di filosofia contemporanea, 2016)
In order to investigate the theme of the impersonal, I would like to draw attention on the last film of Yorgos Lanthimos, The Lobster. After a brief summary of the plot, I will introduce the concept key of littles perceptions, as Deleuze explains it in his monography and in his courses on Leibniz. Supported by the mains sequences of the film, I aim to show how it is possible to understand this concept in terms of perpetual restlessness. Then, I will define this condition not just as the animal condition, but also and mainly as the condition of virtuality, concluding with a reflection on the role of the corporeality.